Mechanical Performance of Blended Fly Ash-based Geopolymer Concrete with GGBS and Metakaolin - Ali Ali; Tareq Al-Attar; Waleed A. Abbas (Engineering and Technology Journal, 2022)
One of the most user-friendly alternatives to ordinary concrete is geopolymer concrete(GPC), which achieves the same result. GPC is a unique substance made by activating source materials with a high concentration of silica and alumina. As a result, geopolymer binders use less raw resources and emit less carbon dioxide. For these reasons, most academics are focusing on these sorts of resins to develop eco-friendly housing. This article reports on an experimental investigation that examined the Mechanical Performance of Blended Fly Ash based Geopolymer concrete at 7,28 and 360 days made with two different activator solution molarities and varying R (SiO2/Al2O3) ratios. Positive findings were seen at a larger percentage of GGBS (36%) with a concentration of a sodium hydroxide solution of 10 M and an R ratio of 2.75, compared with other proportions. The test findings indicate that increasing the concentration of sodium hydroxide (NaOH) solution and R enhances the compressive strength and decreases water absorption of geopolymer concrete.